Short report: Perceptions of causes and common beliefs of autism spectrum disorder in the U.S. (February 2020) - Castillo, Anabel; Cohen, Shana R.; Miguel, Jessica; Warstadt, Melissa F
Highlights: We explored perceptions of ASD among an American sample of participants and how perceptions may differ based on ethnicity and familiarity with ASD. Exploratory factor analyses revealed two factor subscales for etiological beliefs and general views about ASD. Specifically, the factors that emerged were Psychological Causes, External Causes, Symptom Regulation Perceptions and Common Beliefs. Differences among ethnic groups were found in participants' beliefs about Psychological Causes, Symptom Regulation Perceptions, and Common Beliefs. Abstract: A preliminary assessment of public perceptions about autism spectrum disorder (ASD) was conducted across the United States using Mechanical Turk, an online recruitment tool for collecting data anonymously. Participants completed a survey about their beliefs regarding causes, treatments, and general views of ASD. For example, when asked what causes ASD, most participants reported hereditary and neurological factors. Exploratory Factor Analyses (EFAs) revealed two separate two-factor subscales for causes and general views about ASD. Findings revealed ethnic differences in participants' beliefs about Psychosocial Causes, Symptom Regulation Perceptions, and Common Beliefs. Participants that were diagnosed with or had a family member with ASD were more likely to attribute ASD to External Causes than those without those connections to ASD. Implications for policy and practice discuss how study findings might support the development of targeted ASD public awareness campaigns.